Collaborative Value Co-creation in the Platform Economy (Translational Systems Sciences,, 2018)
This book offers a service science perspective on platform orchestration and on collaborative consumption, providing an overview of research topics related to service dominant logic in multi-sided markets. The chapters give an international and multi-disciplinary overview of the current topics of digital service platforms from many angles. This overview helps in filling the gap between service science and recent research of the platform economy and paves the way for future service platform research. Open standards and distributed databases such as blockchain configurations increase the connectivity of business ecosystems as devices and systems exchange data with each other instead of through intermediaries. This exchange opens up opportunities for new value constellations, makes services globally scalable, and connects local service systems as integrated systems of systems. The book brings together established academics from a number of disciplines. This collaboration makes it possible to provide novel constructs and empirical results that help the reader to understand how value is co-created and orchestrated in the era of digital service platforms. In addition to theory building, practical implications for wider managerial and policy use are highlighted. The topics in this book are related to service platform technologies; organizational capabilities; and strategies and management in the contexts of retail, healthcare, and the public sector. A wide selection of case studies is used to demonstrate the implications of platforms for different service and economic contexts. Combining both theory and practice, this book is highly recommended for readers interested in the service and marketing point of view on the platform economy and for practitioners strategizing for scalable service platforms. Chapters 4 and 10 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.